2019
DOI: 10.2147/jpr.s190201
|View full text |Cite
|
Sign up to set email alerts
|

<p>Preoperative ultrasound-guided multilevel paravertebral blocks reduce the incidence of postmastectomy chronic pain: a double-blind, placebo-controlled randomized trial</p>

Abstract: PurposeChronic postsurgical pain is a challenging problem after breast cancer surgery. This prospective, randomized, double-blinded, parallel-group, placebo-controlled trial was conducted to evaluate the influence of preoperative ultrasound-guided multilevel paravertebral blocks (PVBs) on chronic pain following mastectomy.Patients and methodsOne hundred eighty-four women were randomized to receive ultrasound-guided multilevel (T1–T5) PVBs with 5 mL of ropivacaine 0.5% or normal saline per level. The primary en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…However, some studies suggest that early intervention, including improved perioperative analgesia can reduce incidence. One prospective, randomized, double-blinded, placebo-controlled trial showed that one-time preoperative paravertebral blocks with local anesthetic at levels T1-5 before breast cancer surgery reduced risk of persistent pain at three and six months postoperative by 32.6% and 40.5%, respectively (21). We feel PNS of the proximal spinal nerves introduces a novel modality to consider in treating this patient population, as we demonstrated with Patient 1 in our case series.…”
Section: Potential Future Applications In Oncologic Pain Persistent Psupporting
confidence: 56%
See 1 more Smart Citation
“…However, some studies suggest that early intervention, including improved perioperative analgesia can reduce incidence. One prospective, randomized, double-blinded, placebo-controlled trial showed that one-time preoperative paravertebral blocks with local anesthetic at levels T1-5 before breast cancer surgery reduced risk of persistent pain at three and six months postoperative by 32.6% and 40.5%, respectively (21). We feel PNS of the proximal spinal nerves introduces a novel modality to consider in treating this patient population, as we demonstrated with Patient 1 in our case series.…”
Section: Potential Future Applications In Oncologic Pain Persistent Psupporting
confidence: 56%
“…Breast cancer is the most commonly diagnosed cancer among women with five-year survival greater than 90% (19). The prevalence of persistent pain after breast cancer treatment is 25-60% (20,21). Three of the common causes of chronic pain in these patients include intercostobrachial neuralgia from transection of the intercostobrachial nerve during surgery, radiation-induced cutaneous changes, and radiation-induced inflammation (20).…”
Section: Potential Future Applications In Oncologic Pain Persistent Pmentioning
confidence: 99%
“…Theoretically, RA could alleviate acute postoperative pain by blocking peripheral nociceptive input into the spinal cord, which contributed to spinal sensitization. Previous studies have reported that PVB and PECS could reduce incidence of chronic pain after breast surgery [22][23][24]. In a recent meta-analysis, the use of single-shot PVB has been shown to be protective against CPSP at 6 months following BCS, but the studies included are weakened by methodological limitations [12].…”
Section: Discussionmentioning
confidence: 99%
“… Ilfeld et al., 2018 27 Uni- or bilateral mastectomy Ultrasound- guided continuous PVB catheter 12 Presence of pain, pain intensity and interference (BPI) PVB catheter significantly decreased incidence ( P = 0.011 ) and intensity of pain ( P = 0.007 ). Qian et al., 2019 22 Unilateral partial mastectomy Ultrasound-guided single-injection multilevel TPVB 6 Presence of pain, pain intensity and interference (BPI) PVB significantly reduced severity ( P < 0.001 ). and incidence (P = 0.03 ) of chronic pain.…”
Section: Resultsmentioning
confidence: 99%